Biogenic synthesis, characterization of antibacterial silver nanoparticles and its cell cytotoxicity - Gopinath, V.; Priyadarshini, S.; Loke, M.F.; Arunkumar, J.; Marsili, E.; MubarakAli, D.; Velusamy, P.; Vadivelu, J. (Elsevier, 2017)
The advanced research and development of silver nanoparticles (AgNPs) is vast due to their incredible applications today. In this work, AgNPs were synthesized using soil derived Pseudomonas putida MVP2. The AgNPs formation on the P. putida cell membrane and its cell free supernatant was studied. The synthesized AgNPs were characterized by UV–visible spectroscopy, scanning transmission electron microscopy (STEM), X-ray diffraction (XRD), energy dispersive X-ray (EDAX) and Fourier transform infrared (FTIR) spectrum analysis. The mode of action of AgNPs on the bacteria was studied against clinically isolated bacterial pathogens, Staphylococcus aureus, Escherichia coli, Bacillus cereus, Pseudomonas aeruginosa and Helicobacter pylori by membrane integrity, and protein leakage using confocal and electron microscopy. Interestingly, AgNPs had no cytotoxicity under 25 μg/mL and it was toxic at above 50 μg/mL on human epidermoid larynx carcinoma (HEp-2) cells. This study evidenced that biogenic nanoparticles could affect the bacterial replication, protein leakage and eventually cell death. This might be used for active antimicrobial agents for the chronic infections.